Dual-Band Patch Antenna Fed by Meandering Probe for Low Cross-Polarization - Xiao-Lan Zhao; Quan Wei Lin (International Journal of Antennas and Propagation)
This paper presents a dual-band patch antenna loaded with face-to-face U-shaped slots fed by a substrate-integrated meandering probe (SIM-probe). With the presence of U-shaped slots, two current paths are formed, which leads to the resonance modes at 2.4 and 3.65 GHz on the patch. The SIM-probe suppresses the unwanted cross-polarization radiations by providing out-of-phase vertical currents from vertical metallic vias. To verify our work, a prototype was fabricated and tested. The proposed antenna achieves the impedance bandwidths of 9.4% and 9% from the frequency range of 2.34–2.57 GHz and 3.5–3.83 GHz (for the reflection coefficient ≤ −10 dB) and obtains average gains of 5.8 dBi and 6.8 dBi at both bands. The cross-polarization level is below −20 dB. Measured results agree well with the simulation.